Transjugular intrahepatic portosystemic shunt stent-graft placement: mean optimal portal venous projection view determined by three-dimensional portography. (June 2013) - Maleux, Geert; Jiang, X; Heye, S; Mariën, I; Nevens, F; Grünhagen, T
Background: Suboptimal stent-graft placement at the lower anastomosis during transjugular intrahepatic portosystemic shunt (TIPS) may result in early shunt stenosis and occlusion owing to incomplete covering of the parenchymal tract by the covered part of the stent-graft. Purpose: To determine the optimal portal venous projection view for stent-graft placement during TIPS and the potential influence of the portal vein anatomy. Material and Methods: On 76 cirrhotic patients (48 men and 28 women) selected for TIPS, rotational, three-dimensional (3D), catheter-directed angiography of the portal vein was performed. The 3D portograms were reviewed by two independent interventional radiologists to determine the optimal angiographic projection views for stent-graft placement. Intra-observer and inter-observer reliabilities were tested and subgroups of patient portal vein anatomy were categorized. Results: Among all patients, the optimal portal venous projection views for stent-graft placement during TIPS centered around 27° (±14°) right oblique and 3° (±7°) craniocaudal. Of these, 56% were within the standard deviations. Intra-observer reliabilities were 0.60 and 0.62 for the two radiologists, respectively. Inter-observer reliability was 0.48. Anatomical variations in the patient population were: normal portal vein (67%), trifurcation at main portal vein (16%), right posterior portal vein as the first branch of main portal vein (3%), no right posterior portal vein (1%), and other variations (13%). Anatomical subgroups did not influence the best angiographic projection view significantly (F4, 295 = 0.91, P = 0.457). Conclusion: The mean optimal angiographic projection view for TIPS stent-graft placement was 27° right oblique and 3° craniocaudal. Patient anatomic variations do not play a significant role in determining the optimal angiographic view for TIPS stent-graft placement.